Local Exosome Inhibition Potentiates Mild Photothermal Immunotherapy Against Breast Cancer - Qian Chen; Yanan Li; Jiameng Hu; Zhenyu Xu; Shengyi Wang; Naicong Cai; Mengjiao He; Yifang Xiao; Yuan Ding; Mengjuan Sun; Chunjiayu Li; Yiyang Cao; et al. (Advanced Science)
Abstract Limited immune infiltration within the tumor microenvironment (TME) hampers the efficacy of immune checkpoint blockade (ICB) therapy. To enhance immune infiltration, mild photothermal therapy (PTT) is often combined with immunotherapy. However, the impact of mild PTT on the TME remains unclear. The bioinformatics analyses reveal that mild PTT amplifies immune cell infiltration and stimulates T‐cell activity. Notably, it accelerates the release of tumor cell‐derived exosomes (TEX) and upregulates PD‐L1 expression on both tumor cells and TEX. Consequently, it is proposed that locally inhibiting TEX release is crucial for overcoming the adverse effects of mild PTT, thereby enhancing ICB therapy. Thus, a multi‐stage drug delivery system is designed that concurrently delivers photosensitizers (reduced graphene oxide nanosheets, NRGO), anti‐PD‐L1 antibodies, and exosome inhibitors (sulfisoxazole). The system employs a temperature‐sensitive lipid gel as the primary carrier, with NRGO serving as a secondary carrier that supports photothermal conversion and incorporation of sulfisoxazole. Importantly, controlled drug release is achieved using near‐infrared radiation. The findings indicate that this local combination therapy remodels the immunosuppressive TME through exosome inhibition and enhanced immune cell infiltration, while also boosting T‐cell activity to trigger systemic antitumor immunity, showcasing the remarkable efficacy of this combination strategy in eradicating cold tumors.